Supporting decision making in mobile software development: A fuzzy cognitive maps approach - Yiasemis, Pantelis Stylianos; Andreou, Andreas S. (My University, 2013)
Mobile Software Development has rapidly evolved from the closed environments of in-house development performed by the manufacturers of mobile devices to the widely available Software Development Kits that made development available to practically everyone. The easy distribution of applications on online markets like App Store and Google Play makes their development very tempting for developers who move from traditional software to mobile applications. As with desktop systems, mobile application developers face a number of difficult decisions that need to take prior to and during the development process. This paper proposes a decision support model based on Fuzzy Cognitive Maps that assists developers to assess whether they should go ahead and develop a mobile application or not based on a number of factors and specifications. In fact the map models the outcome of the complex interaction between competing factors and estimates which ones will finally prevail. A validation process with realistic and real-world cases proved that the model performs quite successfully.
Keywords: Decision support; Mobile software; Development process; Fuzzy cognitive maps